ASME 2004 Power Conference 2004
DOI: 10.1115/power2004-52036
|View full text |Cite
|
Sign up to set email alerts
|

Underground Coal Gasification for Power Generation: High Efficiency and CO2-Emissions

Abstract: Underground Coal Gasification (UCG) is a gasification process carried out in non-mined coal seams using injection and production wells drilled from the surface, enabling the coal to be converted into product gas. The UCG process practiced by Ergo Exergy is called Exergy UCG or εUCG. εUCG was applied in the Chinchilla UCG-IGCC Project in Australia. The IGCC project in Chinchilla, Australia has been under development since July 1999. The project involves construction of the underground gasifier and demonstration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Permeability, in consideration of the difference between hydrostatic and UCG reactor pressure, controls fluid in-and outflow into and out of the reactor, respectively [31,60]. Figure 4 illustrates that permeability changes resulting from isothermal and non-isothermal simulations exhibit significant deviations in the close UCG channel vicinity.…”
Section: Discussionmentioning
confidence: 99%
“…Permeability, in consideration of the difference between hydrostatic and UCG reactor pressure, controls fluid in-and outflow into and out of the reactor, respectively [31,60]. Figure 4 illustrates that permeability changes resulting from isothermal and non-isothermal simulations exhibit significant deviations in the close UCG channel vicinity.…”
Section: Discussionmentioning
confidence: 99%
“…UCG has numerous economic and environmental benefits [2]. Compared to conventional use of coal, UCG has the same advantages as above-ground gasification.…”
Section: Introductionmentioning
confidence: 99%
“…As result of this surge, knowledge of UCG is sought again and more than 30 trials are conducted or planned in Australia, China, India, South Africa, New Zealand, Canada and the USA. Many of these trials are carried out under technological auspices of Ergo-Exergy -the leading supplier of modern commercial UCG technology and the holder of proprietary rights for the process called εUCG [2].…”
Section: Ucg Surgementioning
confidence: 99%
See 1 more Smart Citation
“…Blinderman and Anderson [12] studied the data of the εUCG process applied to a 10 m thick coal layer at 140 m depth in Chinchilla, Australia. They showed that the overall efficiency of the electricity production from the UCG-IGCC (Integrated Gasification Combined Cycle) can reach 43%, which is comparable to a natural gas combined cycle (NGCC).…”
Section: Introductionmentioning
confidence: 99%